Synthesis and characterization of Fe-modified zeolite for spin conversion of hydrogen at cryogenic temperature - Kim, Jung Hyun; Kang, Sarng Woo; Nah, In Wook; Oh, In-Hwan (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Fe-modified zeolite was prepared by ion-exchange of zeolite with ferric chloride and calcination, for effective spin conversion of ortho- to-para-hydrogen. Studies carried out using BET, SEM, EDS, and VSM techniques. Results indicated that spin conversion rate showed great dependence on magnetic properties of the composite according to calcination temperature change. For lower sintering temperatures, the samples showed more paramagnetic behavior. As sintering temperature increased, ferromagnetic state increase, while paramagnetic states decreased. The highest spin conversion was observed at paramagnetic state, comparing with ferromagnetic, at lower calcination temperature. Moreover, Fe-modified zeolite showed a superior hydrodynamic property such as the pressure drop ratio of composite to a commercial iron oxide. These composites can be applied in more efficient hydrogen liquefaction processes. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CATALYST